Physico-chemical and Bacteriological Water Quality Assessment to the Rivers Iber and Sitnica - Dreshaj, Adem; Beqiraj, Ismet; Feka, Fidan; Malja, Agim; Behrami, Esad; Topi, Dritan (Asian Journal of Chemistry, 2012)
Investigation of the water pollution for the Iber and Sitnica rivers related to the heavy metals, some physico-chemical and bacteriological indicators is presented in this study. Application of analytical techniques, ICP-MS and ICP-OES, were used to determine levels of present chemical elements, including mercury. These techniques offer a more complete multi elementary analysis than other techniques related to the environmental studies. Multi elementary analysis of the samples by ICP-MS and ICP-OES was conducted in the laboratory "ACTLABS" in Ontario, Canada. Microbiological-bacteriological analyses are conducted in the Institute of Public Health, Prizreni Division. Geographical position of samples is determined by the geographic positioning system (GIS). The results show that environmental pollution of surface waters from the studied rivers is considered moderately high. Regarding to the microbiological contamination of the surface waters it depends on residential areas.